Vibrational coherence spectroscopy identifies ultrafast branching in an iron(II) sensitizer - Hainer, Felix; Alagna, N.; Reddy Marri, A.; Penfold, T. J.; Gros, P. C.; Haacke, S.; Buckup, Tiago (The journal of physical chemistry letters, 2021)
The introduction of N-heterocyclic carbene ligands has greatly increased the lifetimes of metal-to-ligand charge transfer states (MLCT) in iron(II) complexes, making them promising candidates for photocatalytic applications. However, the spectrally elusive triplet metal-centered state (3MC) has been suggested to play a decisive role in the relaxation of the MLCT manifold to the ground state, shortening their lifetimes and consequently limiting the application potential. In this work, time-resolved vibrational spectroscopy and quantum chemical calculations are applied to shed light on the 3MCs’ involvement in the deactivation of the MLCT manifold of an iron(II) sensitizer. Two distinct symmetric Fe-L breathing vibrations at frequencies below 150 cm-1 are assigned to the 3MC and 3MLCT states by quantum chemical calculations. On the basis of this assignment, an ultrafast branching directly after excitation forms not only the long-lived 3MLCT but also the 3MC as an additional loss channel.